2x+3=5x+6-9

Simple and best practice solution for 2x+3=5x+6-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3=5x+6-9 equation:


Simplifying
2x + 3 = 5x + 6 + -9

Reorder the terms:
3 + 2x = 5x + 6 + -9

Reorder the terms:
3 + 2x = 6 + -9 + 5x

Combine like terms: 6 + -9 = -3
3 + 2x = -3 + 5x

Solving
3 + 2x = -3 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
3 + 2x + -5x = -3 + 5x + -5x

Combine like terms: 2x + -5x = -3x
3 + -3x = -3 + 5x + -5x

Combine like terms: 5x + -5x = 0
3 + -3x = -3 + 0
3 + -3x = -3

Add '-3' to each side of the equation.
3 + -3 + -3x = -3 + -3

Combine like terms: 3 + -3 = 0
0 + -3x = -3 + -3
-3x = -3 + -3

Combine like terms: -3 + -3 = -6
-3x = -6

Divide each side by '-3'.
x = 2

Simplifying
x = 2

See similar equations:

| 108=9(x-5) | | -8x+2=8-7x | | k-(-4)=-2 | | -5(3r+2)=-130 | | 4[z(x+3)+7]-5x=61 | | -8(1+n)=16 | | 351=27v | | 12=n-2 | | -(x+5)(x+5)+(x-4)(x-4)+5(2x+5)=-5(x+2)(x-2) | | -4+4x=3x+3 | | -3=x+-7 | | 5x-12y=0 | | 2x^2-8x-10x=-10 | | 6x=70+x | | x^3+3=5x | | 15=6-2x-x | | -15=m+-15 | | 4ab-2a-2b+1= | | -7=-9+x/7 | | 4a+20=48 | | -44=4v-8 | | x^3+3=5 | | 1=v+(-2) | | 16x-9x=42 | | 3u-7=-22 | | 8+2w=-6 | | 4x+33=8x-3 | | 16=-3y-5y | | 1x^2+5x+6=3 | | (x^4)+4=0 | | x=-10+2y | | 6x+17=-24-6x |

Equations solver categories